A prospective study on combined lymphedema surgery: Gastroepiploic vascularized lymph nodes transfer and lymphaticovenous anastomosis followed by suction lipectomy. Issue 1 (26th August 2020) - Di Taranto, Giuseppe; Bolletta, Alberto; Chen, Shih‐Heng; Losco, Luigi; Elia, Rossella; Cigna, Emanuele; Rubino, Corrado; Ribuffo, Diego; Chen, Hung‐Chi
Abstract: Background: There is no consensus on the appropriate treatment of lymphedema. Proposed techniques include lymphaticovenous anastomosis (LVA), vascularized lymph nodes transfer (VLNT), and suction lipectomy (SL). The benefit of combined procedures has also been postulated. In this prospective study, a combined protocol is proposed as an alternative to single‐procedure strategies. Methods: Between January 2016 and October 2018, we enrolled patients with secondary lymphedema of lower limbs, stage II‐III according to the International Society of Lymphology, progressive swelling and skin tonicity >60. Thirty‐seven consecutive patients were dichotomized into group I, undergoing VLNT, and group II undergoing VLNT and LVA. Gastroepiploic lymphnode flap was harvested through laparoscopy, and in the same operation, LVAs were performed in group II on the basis of indocyanine green lymphography and patent blue findings. Two weeks later, SL was performed in all the patients. Patients were prospectively evaluated through clinical examination, circumference measurement, and skin tonicity. Results: The average follow‐up was 2 ± 0.8 years. The first consecutive 21 patients were treated with VLNT followed by SL. The next 16 patients underwent combined VLNT and LVA, followed by SL. A mean of 2.4 LVAs were performed. A significant difference in the postoperative circumference measurements was found overall ( p < .05): 52.6 ± 18.9 above the knee, 42.9 ± 25 below the knee, 36.2 ± 37 at foot. The postoperative tonicity dropped by 12.7 ± 6.3% ( p < .05). The episodes of cellulitis significantly decreased to 0.1 ± 0.3 ( p < .05). Conclusions: LVA, VLNT, and SL can be integrated together in a combined approach, in synergy to enhance the outcomes.